External Debt and Growth Dynamics in Nigeria - Adamu, I.M.; Rasiah, R. (Blackwell Publishing, 2016)
This paper investigates the dynamic effects of external debt on economic growth in Nigeria from 1970 through 2013. We begin by constructing an external debt sustainability index using principal component analysis to capture the overall effects of external debt indicators on economic growth. The empirical analysis is based on the ARDL bound test. The results show a long-run cointegration relationship between the variables. While external debt exerts an adverse effect of −0.069 per cent on growth in the long run, the external debt sustainability index shows a positive effect of 0.072 per cent and 0.024 per cent on growth in the long and short run. The findings suggest the government should reduce its expenditure and mobilize revenue through domestic sources to invest in projects with a high rate of return to enable debt repayment and stimulate growth. To maintain debt ratios within a manageable threshold so as to avoid being debt trapped, foreign loans should only be contracted on concessional terms.